The Implementation of ARCS Learning Model to Improve Students Learning Activities and Outcomes in Vocational High School - Dwi Jatmoko; Arif Susanto; Riawan Yudi Purwoko; Zainal Arifin; Purnawan Purnawan (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2021)
Current learning is needed to emphasize student activities to be more constructive. However, learning emphasizes more on the target material and focuses on the final result. This study aims to improve student learning activities and outcomes in Automotive Engineering Basic Work subjects by implementing the ARCS learning model. This type of research is classroom action research, each cycle consisting of stages of planning, action, observation, and reflection. The research subjects were 40 students of tenth grade State Vocational High School in Purworejo, Indonesia. Data were collected through observation to determine the description of student activities during the learning process. Then the evaluation test was used to determine the final results of student learning after being given the ARCS learning model in the classroom. The study results indicate that the implementation of ARCS learning in the process provides progress on student learning activities and outcomes during the learning process. The results showed that the implementation of the ARCS model increased student learning activities by 74% and increased learning outcomes by 82%. Thus, it can be concluded that the ARCS learning model, in general, can have a potential effect because students are more constructive in learning so that it can be used as a learning reference in vocational high school.